Representative agricultural pathways and scenarios: a trans-disciplinary approach to agricultural model inter-comparison, improvement and climate impact assessment - Valdivia RO; Antle, John M.; Claessens, Lieven; Nelson, Gerald C.; Rosenzweig, Cynthia; Ruane, Alex C.; Vervoort, Joost M. (2013)
The global change research community has recognized that new pathway and scenario concepts are needed to implement impact and vulnerability assessment that is logically consistent across local, regional and global scales. For impact and vulnerability assessment, new socio-economic pathway and scenario concepts are being developed. Representative Agricultural Pathways (RAPs) are designed to extend global pathways to provide the detail needed for global and regional assessment of agricultural systems. RAPs are based on the integrated assessment framework developed by the Agricultural Model Inter-comparison and Improvement Project (AgMIP). This framework shows that both bio-physical and socio-economic drivers are essential components of agricultural pathways and logically precede the definition of adaptation and mitigation scenarios that embody associated capabilities and challenges. This approach is based on a trans-disciplinary process for designing pathways and then translating them into parameter sets for bio-physical and economic models that are components of agricultural integrated assessments of climate impact, adaptation and mitigation. RAPs must be designed to be part of a logically consistent set of drivers and outcomes from global to regional and local. Global RAPs are designed to be consistent with higher-level global socio-economic pathways, but add key agricultural drivers such as agricultural growth trends that are not specified in more general pathways, as illustrated in a recent inter-comparison of global agricultural models. To create pathways at regional or local scales, further detail is needed. At this level, teams of scientists and other experts with knowledge of the agricultural systems and regions work together through a step-wise process. AgMIP has developed spreadsheet-based tools to facilitate this process, to record supporting documentation, and to convert qualitative narratives into parameter sets of models. Examples from AgMIP Regional Teams are used to discuss how the RAPs procedures can be further developed and improved, and how RAPs can help engage stakeholders in climate-related research throughout the research process and in communication of research results.